2021
DOI: 10.3390/computers10110137
|View full text |Cite
|
Sign up to set email alerts
|

Affecting Young Children’s Knowledge, Attitudes, and Behaviors for Ultraviolet Radiation Protection through the Internet of Things: A Quasi-Experimental Study

Abstract: Prolonged exposure to ultraviolet (UV) radiation is linked to skin cancer. Children are more vulnerable to UV harmful effects compared to adults. Children’s active involvement in using Internet of Things (IoT) devices to collect and analyze real-time UV radiation data is suggested to increase their awareness of UV protection. This quasi-experimental pre-test post-test control group study implemented light sensors in a STEM inquiry-based learning environment focusing on UV radiation and protection in primary ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Older students potentially have stronger views on events and venues represented in the digital tour, which are difficult to change as a result of a short interaction with the tool. In contrast, the literature supports that young children's attitudes can be positively affected even through relatively short term digital interventions at the primary education level [30], [31]. Therefore, there is support, both from the literature and from the present study's findings, for targeting young children in future, large-scale interventions attempting to resolve conflictual pasts and lead to social change through the use of virtual tours.…”
Section: Discussionsupporting
confidence: 40%
“…Older students potentially have stronger views on events and venues represented in the digital tour, which are difficult to change as a result of a short interaction with the tool. In contrast, the literature supports that young children's attitudes can be positively affected even through relatively short term digital interventions at the primary education level [30], [31]. Therefore, there is support, both from the literature and from the present study's findings, for targeting young children in future, large-scale interventions attempting to resolve conflictual pasts and lead to social change through the use of virtual tours.…”
Section: Discussionsupporting
confidence: 40%
“…Data sources included questionnaires on UV knowledge, attitudes, and behaviors administered pre-and post-intervention. Preliminary results of this first pre-test post-test control group study with 31 participants were promising, as statistically significant learning gains, and positive behavioral changes were found only for the experimental group (Theodosi & Nicolaidou, 2021).…”
Section: Introductionmentioning
confidence: 87%
“…For the study's second aim, a critical comparison was performed between activities included in Study 1 (Theodosi & Nicolaidou, 2021) and enhanced activities that will be included in its re-enactment in Study 2, in which a commercial e-learning platform (Nearpod) will be used so students can access their learning materials online and work at their own pace.…”
Section: Methodsmentioning
confidence: 99%
“…As we all know, the new network media has won widespread attention from the beginning of its birth, and has continuously developed into one of the key research objects. Literature through the research on the development of information technology after the 20th century, it is found that with the continuous development of informatization, the radiation effect of the Internet has gradually mapped to the global scope [1]. Literature regards the Internet as the main representative of the new media, analyzes and summarizes the decentralization influence of the Internet, and draws a series of conclusions [2].…”
Section: Related Workmentioning
confidence: 99%